Growth dynamics in Acropora cervicornis and A. prolifera in southwest Puerto Rico - Ernesto Weil; Nicholas M. Hammerman; Rebecca L. Becicka; Juan Jose Cruz-Motta (PeerJ, 2020)
Natural population recovery of Acropora palmata, A. cervicornis and their hybrid, Acropora prolifera, have fluctuated significantly after their Caribbean-wide, disease-induced mass mortality in the early 1980s. Even though significant recovery has been observed in a few localities, recurrent disease outbreaks, bleaching, storm damage, local environmental deterioration, algae smothering, predation, low sexual recruitment and low survivorship have affected the expected, quick recovery of these weedy species. In this study, the status of three recovering populations of A. cervicornis and two of A. prolifera were assessed over one year using coral growth and mortality metrics, and changes in their associated algae and fish/invertebrate communities in three localities in the La Parguera Natural Reserve (LPNR), southwest coast of Puerto Rico. Five branches were tagged in each of 29, medium size (1–2 m in diameter) A. cervicornis and 18 A. prolifera colonies in the Media Luna, Mario and San Cristobal reefs off LPNR. Branches were measured monthly, together with observations to evaluate associated disease(s), algae accumulation and predation. A. cervicornis grew faster [3.1 ± 0.44 cm/month (= 37.2 cm/y)] compared to A. prolifera [2.6 ± 0.41 cm/month (= 31.2 cm/y)], and growth was significantly higher during Winter-Spring compared to Summer-Fall for both taxa (3.5 ± 0.58 vs. 0.53 ± 0.15 cm/month in A. cervicornis, and 2.43 ± 0.71 vs. 0.27 ± 0.20 cm/month in A. prolifera, respectively). Algal accumulation was only observed in A. cervicornis, and was higher during Spring-Summer compared to Fall-Winter (6.1 ± 0.91 cm/month and 3.8 ± 0.29 cm/month, respectively, (PERMANOVA, df = 2, MS = 10.2, p = 0.37)). Mortality associated with white band disease, algae smothering and fish/invertebrate predation was also higher in A. cervicornis and varied among colonies within sites, across sites and across season. The balance between tissue grow and mortality determines if colonies survive. This balance seems to be pushed to the high mortality side often by increasing frequency of high thermal anomalies, inducing bleaching and disease outbreaks and other factors, which have historically impacted the natural recovery of these taxa in the La Parguera Natural Reserve in Puerto Rico and possibly other areas in the region. Overall, results indicate variability in both growth and mortality rates in both taxa across localities and seasons, with A. cervicornis showing overall higher mortalities compared to A. prolifera.